Deaths: Leading Causes for 2017 - Heron, Melonie (National vital statistics reports, 2019)
Objectives-This report presents final 2017 data on the 10 leading causes of death in the United States by age, sex, race, and Hispanic origin. Leading causes of infant, neonatal, and postneonatal death are also presented. This report supplements "Deaths: Final Data for 2017," the National Center for Health Statistics' annual report of final mortality statistics. Methods-Data in this report are based on information from all death certificates filed in the 50 states and the District of Columbia in 2017. Causes of death classified by the International Classification of Diseases, 10th Revision (ICD-10) are ranked according to the number of deaths assigned to rankable causes. Cause-of-death statistics are based on the underlying cause of death. Results-In 2017, the 10 leading causes of death were, in rank order: Diseases of heart; Malignant neoplasms; Accidents (unintentional injuries); Chronic lower respiratory diseases; Cerebrovascular diseases; Alzheimer disease; Diabetes mellitus; Influenza and pneumonia; Nephritis, nephrotic syndrome and nephrosis; and Intentional self-harm (suicide). They accounted for 74% of all deaths occurring in the United States. Differences in the rankings are evident by age, sex, race, and Hispanic origin. Leading causes of infant death for 2017 were, in rank order: Congenital malformations, deformations and chromosomal abnormalities; Disorders related to short gestation and low birth weight, not elsewhere classified; Newborn affected by maternal complications of pregnancy; Sudden infant death syndrome; Accidents (unintentional injuries); Newborn affected by complications of placenta, cord and membranes; Bacterial sepsis of newborn; Diseases of the circulatory system; Respiratory distress of newborn; and Neonatal hemorrhage. Important variations in the leading causes of infant death are noted for the neonatal and postneonatal periods.Objectives-This report presents final 2017 data on the 10 leading causes of death in the United States by age, sex, race, and Hispanic origin. Leading causes of infant, neonatal, and postneonatal death are also presented. This report supplements "Deaths: Final Data for 2017," the National Center for Health Statistics' annual report of final mortality statistics. Methods-Data in this report are based on information from all death certificates filed in the 50 states and the District of Columbia in 2017. Causes of death classified by the International Classification of Diseases, 10th Revision (ICD-10) are ranked according to the number of deaths assigned to rankable causes. Cause-of-death statistics are based on the underlying cause of death. Results-In 2017, the 10 leading causes of death were, in rank order: Diseases of heart; Malignant neoplasms; Accidents (unintentional injuries); Chronic lower respiratory diseases; Cerebrovascular diseases; Alzheimer disease; Diabetes mellitus; Influenza and pneumonia; Nephritis, nephrotic syndrome and nephrosis; and Intentional self-harm (suicide). They accounted for 74% of all deaths occurring in the United States. Differences in the rankings are evident by age, sex, race, and Hispanic origin. Leading causes of infant death for 2017 were, in rank order: Congenital malformations, deformations and chromosomal abnormalities; Disorders related to short gestation and low birth weight, not elsewhere classified; Newborn affected by maternal complications of pregnancy; Sudden infant death syndrome; Accidents (unintentional injuries); Newborn affected by complications of placenta, cord and membranes; Bacterial sepsis of newborn; Diseases of the circulatory system; Respiratory distress of newborn; and Neonatal hemorrhage. Important variations in the leading causes of infant death are noted for the neonatal and postneonatal periods.